The Correlation between Exercise Habit and Working Period and WMSDs Complaint on Brickmakers - Arifin, Asyhara Naela; Kristiana, Dita; Dewi, Maya Shyntya (Ikatan Fisioterapi Indonesia, 2022)
Introduction: The study aims to determine the correlation between exercise habit and working period and complaints of work-related musculoskeletal disorders in brickmakers, Work Related Musculoskeletal Disorders are complaints felt by workers on skeletal muscles, resulting in damage to ligaments, joints, and tendons. Brickmakers create bricks for use as building materials, the workers must perform difficult tasks for extended periods of time in uncomfortable positions, and they are not ergonomically at risk of developing WMSDS complaints, these activities require a healthy body which can be obtained from regular exercise habits, brickmakers exercise infrequently and regularly, the average working period of brickmakers is 20 years, a minimum of 3 years and a maximum of 50 years, with a working duration of 10 hours.Methodology: The study was quantitative research with analytical observational method. This research design was cross-sectional with total sampling method. The samples were brickmakers in Potorono Village, Banguntapan, Bantul, Yogyakarta. The total respondents were 30 people. The statistical test used Chi – Square. The variables studied were exercise habits, working period, and WMSDS complaints. The research instrument employed Nordic Body Maps.Research findings: Respondents with moderate WMSDS complaints were 8 respondents (26.7%), respondents with high complaints were 8 respondents (26.7%). The results of the Chi-Square test showed that there was no significant correlation between exercise habits (0.302 > 0.05), working period (0.172 > 0.05) and WMSDS complaints in brickmakers. Conclusions: There is no significant correlation between exercise habits and working period and WMSDS complaints on brickmakers. In field of Physiotherapy, can provide knowledge related to the dangers of work that is not ergonomic, and explanations about the prevention of WMSDS.